OPTIMIZATION OF ECONOMIC LESS CONTACT THROUGH DIGITAL MARKETING TECHNIQUES IN MSME INDUSTRY AT SIMO DISTRICT, BOYOLALI REGENCY - TOPAN SETIAWAN; FANNY HENDRO ARYO PUTRO (CV KULTURA DIGITAL MEDIA, 2021)
ABSTRACT The actual contemporary reality of the economy in Indonesia, one of which is the low purchasing power of the people as a result of the COVID-19 pandemic. When traditional marketing requires physical interaction as a manifestation of economic activity, during a pandemic, physical interaction is so limited, and even then, health protocols must be carefully considered. On the other hand, it must be acknowledged that the MSME industry is one of the economic sectors affected by the pandemic, even though this sector can actually survive in a crisis. Marketing of the results of the MSME industry so far has tended to be conventional, so that the pandemic period is felt to be a hindrance for active and dynamic business processes in the industry. An exit strategy must be developed so that economic activities in the MSME sector can gradually move towards normal reality and are expected to develop rapidly. One way is to implement a less contact economy, where economic transactions are no longer with massive and intense physical interactions, but with mediation vehicles by technological instruments. In this research, one of the MSME industries affected by the COVID-19 pandemic or the corona virus is the MSME association in Simo sub-district, Boyolali district. The association called Focus (Micro, Small and Medium Enterprises Forum - Simo Tangguh) has 40 business units, which currently cannot work optimally. The purpose of this study is to describe the use of digital marketing techniques to market MSME products in Simo sub-district, Boyolali district. Besides that, he also wants to try to optimize the use of digital marketing techniques for MSMEs in the industrial area. This research was conducted with a qualitative method. The qualitative method is expected to be able to produce an in-depth description of the speech, writing, and observable behavior of an individual, group, community, or organization in a particular setting context which is studied from a complete, comprehensive and holistic point of view. This study observes and describes the understanding of the use of digital marketing media in the development of MSME marketing in Simo sub-district, Boyolali